Effect of traditional Chinese medicine monomers interfering with quorum-sensing on virulence factors of extensively drug-resistant Acinetobacter baumannii - Zeng, Li; Lin, Fei; Ling, Baodong (Frontiers in Pharmacology, 2023)
The antimicrobial resistance of Acinetobacter baumannii clinical isolates has emerged as a great threat to public health. Quorum sensing (QS) is one of the resistance mechanisms for drug-resistant A. baumannii. Interfering with QS is a promising strategy to combat infections caused by drug-resistant bacteria. This study explored the QS inhibition ability of thirty-four traditional Chinese medicine monomers (TCMMs) and assessed the effect of QS inhibitors (QSIs) on the virulence factors of twelve extensively drug-resistant A. baumannii (XDRAB) strains. Nine TCMMs, such as caffeic acid, cinnamic acid, and myricetin, were found to be able to strongly inhibit the bacterial QS. Then, at 1/8 of the minimal inhibitory concentration, we found that these QSIs inhibited XDRAB adhesion and biofilm formation and down-regulated the expression levels of virulence-associated genes (abaI, abaR, csuE, pgaA and bap). In conclusion, nine TCMMs have significant QS inhibitory activity and may down-regulate QS genes to interfere with the QS system, which could inhibit the expression of XDRAB virulence factors. These results suggest that TCMMs could develop as novel anti-virulence compounds to control XDRAB infections.